2018
DOI: 10.5539/gjhs.v10n3p172
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent School-Based Sexual Health Education and Training: A Literature Review on Teaching and Learning Strategies

Abstract: Objectives: The objective of this review is to gain an understanding of the teaching approaches used and their effectiveness in imparting sexual health literacy amongst school adolescents. The intention is to design interventions for effective sexual health education in our study setting. Methods:We reviewed various literature related to adolescent sexual health education studies that have been conducted by prior researchers. We also provide an overview of the teaching and learning methods used.Results: Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 33 publications
(39 reference statements)
0
30
0
1
Order By: Relevance
“…into non-gaming context for the purpose of engaging, motivating, promoting to learn, and solving a certain problem. Even prior research suggested gamification could be applicable in sexual health education among adolescents [22]. This study employed different game elements readily added on the Moodle platform.…”
Section: Overview Of the Research Proceduresmentioning
confidence: 99%
“…into non-gaming context for the purpose of engaging, motivating, promoting to learn, and solving a certain problem. Even prior research suggested gamification could be applicable in sexual health education among adolescents [22]. This study employed different game elements readily added on the Moodle platform.…”
Section: Overview Of the Research Proceduresmentioning
confidence: 99%
“…Despite the various sexual health educational initiatives, the delivery and implementation of sexual health education is still controversial in resource-limited settings. Irresponsible adolescent sexual health behaviour and the resultant adverse health effects are on the rise in developing countries [ 9 , 13 , 14 ]. The inadequate comprehensive adolescents’ sexual well-being knowledge and skills make them more likely to engage in unhealthy sexual behavior [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inadequate implementation of sexual health education in school is due to various factors, including social and cultural attitudes that do not allow open discussion and teachers’ resistance to teaching sexual health matters [ 14 ]. Furthermore, the existing, widely employed traditional teaching methods do not support the effective delivery of sexual health education [ 13 , 18 ]. Adequately accessible sexual health education could help to protect adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations